Extraction and Characterization of Nanosilica from Young Bamboo Leaf Ash Using Various Solvents - Anis Mahmudah Nabila Diena; Mirza Aqeel Fernanda; Susilowati; Silvana Dwi Nurherdiana; Sani; Sintha Soraya Santi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Young bamboo leaves represent a promising biomass resource for silica production owing to their high silica content. This study aims to determine the effects of different alkali solvents on the extraction and synthesis of nanosilica from young bamboo leaf ash using hydrothermal and sol-gel methods. Young bamboo leaf ash was calcined at 700°C for 4 hours, then extracted with NaOH, KOH, and Na?CO? solutions at 1–3 N at 85°C for 3 hours. The extracted filtrate was then hydrothermally processed at 120°C for 6 hours. Nanosilica synthesis was carried out using the sol-gel method by adding a 1 N HCl solution until the gel reached pH 7 to precipitate silica in gel form, then drying at 110°C to obtain nanosilica powder. The resulting product was characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). The XRF analysis of the raw material showed a SiO? content of 68.6%, indicating that young bamboo leaf ash has potential as a source of silica. The highest yield was obtained with 1.5 N NaOH at 94.40%, followed by 1.5 N KOH at 72.59% and 2 N Na?CO? at 24.87%. XRF characterization of the product showed a SiO? content of 62.059%. The XRD results indicated that the resulting silica was dominated by an amorphous phase with a small crystalline phase, while the SEM-EDX analysis showed a dominance of Si and O elements and agglomerated particle morphology with particle sizes ranging from 206.5–563.7 nm. Based on the research results, 1.5 N NaOH is the most effective solvent for producing nanosilica from young bamboo leaf ash. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action